The Synergy Between Corrosion and Fatigue: Failure Analysis of an Aerator and a Cooling Tower - da Rocha Magalhães, Luciano; da Silva Alvarenga, Rodrigo Freitas; Resende, Flávio Augusto Coelho; da Silva, Leonardo Rosa Ribeiro; Filho, Waldek Wladimir Bose; Franco, Sinésio Domingues (Journal of failure analysis and prevention, 2023)
Corroded points can act as stress concentrators, usually resulting in the component failure at fewer cycles than was initially projected. Aerators are widely used in waste treatment units for chemical and biological control. Due to the chemically aggressive environment to which these components are subjected, they usually fail due to corrosion in one or more components. Cooling towers are one of the most applied equipment for temperature control in industrial processes. Due to generally hostile environments and operating conditions, this equipment is subject to failures which almost always lead to system imbalance followed by the catastrophic failure of the component. This work investigates the synergic effect of corrosion and fatigue in two separate case studies. In the first, the wear of the mixing shaft of an aerator was investigated. It was observed that the root cause of wear was the corrosion of the dissimilar welded joints in the mixing blades, which suffered the sensitization phenomenon. This sensitization led to the formation of accentuated corrosion pits, which concentrated stresses and led to the failure of the welded joint. After the joint failure, the component was left in an unbalanced state, which resulted in severe wear on the mixer shaft of the aerator. In the second, the failure of a cooling tower fan shaft fracture was evaluated, with the fractured component being compared to an intact one. As means of analysis were employed: metallographic tests on macroscopic and microscopic scales, tensile, chemical composition, hardness tests, and fractography. The results indicated the component failure due to fatigue under low amplitude loading, with corrosion pits as stress intensifiers.